The home environment and parental involvement of preschoolers in Philippi, a low-income area: Do they hinder or support early learning? - Amiena Bayat; Siphe Madyibi (South African Journal of Childhood Education, 2022)
Background: Successful interventions targeting families can only occur through informed research findings. It is important that policymakers understand the unique household dynamics that low-income households face and the kinds of assistance they need to foster early learning and development at home.